[Eu(tta)3(Phen-derived)] complexes: Theoretical and empirical approaches enlightening their photophysical behavior - Silva, Rodolpho A.N. [UNESP]; Menezes, Jean D.C. [UNESP]; Marineli, Gyovanna C. [UNESP]; Cebim, Marco A. [UNESP]; Davolos, Marian R. [UNESP]; Lima, Sergio A.M. [UNESP]; Pires, Ana M. [UNESP] (Elsevier, 2024)
Motivated by the high demand for efficient luminescent systems, whether new or little explored, a series of complexes based on the Eu3+ ion, coordinated with the β-diketone 4,4,4-trifluoro-1-(thiophen-2-yl)butane-1,3-dione, and several 1,10-phenanthroline derivatives (PIB, PIB_4CH3, and PIN_2OH), were synthesized, characterized, and had their optical properties evaluated using PLS. The complex containing the PIB ligand, although already reported in the literature, had its photophysical properties explored in depth and compared with those of the other complexes introduced here. The complexes containing the ligands PIB and PIB_4CH3 exhibited the highest intrinsic quantum yield values, 38.7% and 41.8%, respectively; the one containing the ligand PIN_2OH the lowest value, 16.6%, and the precursor complex [Eu(tta)3(H2O)2] an intermediate value of 28.1%. Computational calculations suggest that in the complexes containing the ligands PIB and PIB_4CH3 there is no significant back-transfer, justifying their higher values of quantum yield. However, when the PIN_2OH ligand is used, back-transfer occurs strongly between the T1 and 5D1 states, decreasing its performance in relation to the others. Therefore, the choice of the PIB ligand was appropriate to increase the emission efficiency of the complex, and among the new ligands introduced, PIB-4CH3 was the most promising for applications involving luminescent emitters.
Keywords: Luminescent materials; Molecular systems; Optical spectroscopy